The General Directorate of Press and Dissemination of the Ministry of Foreign Affairs: its propaganda strategy to confront the 'anti-Argentina campaign' (1977-1981) (Quinto Sol, 2024)
This work examines the foreign communication and propaganda strategy of the last Argentine dictatorship developed by the General Directorate of Press and Diffusion established in 1977 in the Foreign Ministry. Its operation is investigated based on the discovery of a series of folders produced by this agency. We reflect on the drift of this documentation to subsequently analyze its content. This allows us to identify the invitation program for foreign journalists selected to visit Argentina. Those chosen were not only identified figures and defenders of the regime, but also those who expressed more critical positions and those who were capable of producing “non-political” tourist chronicles. His journalistic writings, in turn, allow us to point out invariants (common features) that lead to identifying guidelines of the communication project of the dictatorship.Finally, this work focuses on the peculiar functioning of this Directorate: the presence, among its employees and officials, of women who were prisoners in one of the main clandestine detention centers – the Navy Mechanics School – and who were transferred to the Chancellery to work. Their inscriptions in the documents lead us to reflect on the work with bureaucratic-administrative documentation produced by the terrorist State.
Keywords: international relations; dictatorship; propaganda; diplomacy